FAKTOR YANG BERHUBUNGAN DENGAN GANGGUAN KULIT PADA PETANI DI DESA SUMURAN TAPANULI SELATAN - Novita Aryani; Sisca Dwi Ningsih; Normi Parida Sipayung (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
The incidence of skin disorders due to work shows an increase in cases every year. The percentage of contact dermatitis from all occupational diseases is at the top of the list at 50-60%. Many factors can cause skin disorders while working. The purpose of this study was to determine the knowledge, attitudes and actions of farmers related to skin disorders experienced by farmers in Sumuran Village, Batang Toru District, South Tapanul Regency. The research method is a quantitative type with a cross-sectional approach. The population in the study were farmers in Sumuran Village, namely 334 people. The number of samples was taken using Yount's table, namely 10% of the total population, while the sampling method was accidental sampling. Retrieval of data using a questionnaire containing 25 questions. The results showed that there was a relationship between knowledge (p-value = 0.001), attitude (p-value = 0.017), and action (p-value = 0.011) with the incidence of cultural disturbances in farmers. The conclusion that knowledge , attitudes and actions of farmers in Sumuran Village, Batang Toru District, South Tapanuli Regency, have a relationship with the occurrence of skin disorders.